Twelve-step Spirituality in View of the Sacrament of Reconciliation in the Catholic Church - Andrzej Jastrzębski (Polonia Sacra)
This article ventures into the basic principles of the original Twelve-step program by studying its similarity with the dynamics of the Sacrament of Reconciliation in the Catholic Church. It begins with a short presentation of the theological foundation of confession, and continues with the history of AA’s Twelve-step recovery program while focusing on the latter’s spiritual dimension and that of similar groups. The major analysis is dedicated to demonstrating and discussing the parallels found in the twelve steps content and the Sacrament of Reconciliation; where the twelve steps have their effectiveness written within themselves, the Sacrament of Reconciliation also requires a progression from contrition, an examination of conscience, the confessing sins and satisfaction. In conclusion, the author presents pastoral suggestions meant to facilitate work with believers struggling with various addictions.